Künstler Plakate : Katalog nr.5 - Lempert, Herbert Fritz (Bonn : Galerie für Moderne Kunst und Plakatkunst, 1991)
ABR ; Adami, Valerio ; Albers, Josef ; Alechinsky, Pierre ; Alt, Otmar ; ALviani, Getulio ; Andre, Carl ; Antes, Horst ; Anuskiewicz, Richard ; Appel, Karel ; Arakawa, Shusaku ; d'Arcangelo, Allan ; Arman ; Armleder, John M. ; Arp, Hans ; Arroyo, Eduardo ; Artschwager, Richard ; Ashbaugh, Dennis ; Attersee, Christian Ludwig ; Bacon, Francis ; Baechler, Donald ; Bailey, William ; etc.
Künstler Plakate : Katalog nr.5, Galerie für Moderne Kunst und Plakatkunst, Bonn, 1991
boek